MEMBANGUN KESADARAN LINGKUNGAN BERDASARKAN PENDIDIKAN ISLAM - Riska Ristiana (Institut Agama Islam Insan Prima Misbahul Ulum Gumawang OKU Timur Sumatera Selatan, 2025)
Environmental awareness has become a crucial issue in addressing increasingly complex ecological problems. Islamic education holds great potential in shaping a community that is concerned about the environment through the integration of Islamic values. This article aims to examine how Islamic education can systematically and sustainably build environmental awareness. This study employs a qualitative approach through a literature review of various recent scientific journals. The findings indicate that the development of environmental awareness in Islamic education can be carried out through the internalization of the values of amanah (trust), khalifah (stewardship), and ihsan (excellence); the implementation of environmentally-based curricula; and the active role of educational institutions in cultivating a culture of environmental care. The integration of Islamic-based environmental education contributes to the formation of a generation that is both religious and ecologically conscious.